Efficacy and safety of recombinant zona pellucida vaccines in domestic horse mares and current application of native porcine zona pellucida vaccines in African elephant cows - Schulman, Martin L. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.